2017
DOI: 10.3389/fcimb.2017.00018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Murine Cervicovaginal Infection by Chlamydial Strains: Identification of Extrusions Shed In vivo

Abstract: Chlamydia trachomatis is the leading cause of bacterial sexually transmitted infections (STIs) and preventable blindness. Untreated, asymptomatic infection as well as frequent re-infection are common and may drive pelvic inflammatory disease, ectopic pregnancy, and infertility. In vivo models of chlamydial infection continue to be instrumental in progress toward a vaccine and further elucidating the pathogenesis of this intracellular bacterium, however significant gaps in our understanding remain. Chlamydial h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
0
12
1
Order By: Relevance
“…Therefore, recruitment of host MYPT1 to the inclusion by CT228 serves to regulate the manner and degree of host cell egress. Although the extrusion process has been observed in vitro for many years (Todd and Caldwell, 1985 ; Hybiske and Stephens, 2007 , 2008 ), it was only recently documented to occur in vivo across multiple serovars (Shaw et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, recruitment of host MYPT1 to the inclusion by CT228 serves to regulate the manner and degree of host cell egress. Although the extrusion process has been observed in vitro for many years (Todd and Caldwell, 1985 ; Hybiske and Stephens, 2007 , 2008 ), it was only recently documented to occur in vivo across multiple serovars (Shaw et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that extrusions are readily phagocytosed by macrophages where they show enhanced survival and may contribute to dissemination [ 44 ]. In vivo evidence of extrusions have also been detected using a cervicovaginal infection model suggesting relevance to active infections [ 45 ]. Recognition of the signaling pathways influencing the different exit strategies should provide insights into the regulation of chlamydial dissemination during disease.…”
Section: Discussionmentioning
confidence: 99%
“…The EB cell type is wholly responsible for initiating new rounds of infection, mediating cell entry and initiating the creation of the intracellular replication niche, while the RB cell type replicates and initiates differentiation to the EB cell type to prepare for release and reinfection. The production of the EB cell type is asynchronous, leading to EBs of vastly different ages present in the inclusion until released by host cell lysis or extrusion of the inclusion (32). The release of chlamydial EBs at the end of the intracellular developmental cycle by the aforemen- tioned mechanisms has been the focus of research for several decades.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of chlamydial infectivity within both the inclusion and extracellular environments has only received minimal attention, likely in part due to the long-held view that the chlamydial EB is metabolically inert. Indeed, the more recently introduced concept of the extrusion of intact inclusions (32,36), in addition to the release of EBs from the host by lysis, has been presented as a potential mechanism for chlamydiae to survive for longer periods of time following release from the host cell.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation